2020
DOI: 10.1038/s41598-020-77151-6
|View full text |Cite
|
Sign up to set email alerts
|

Initial assessment of treatment of talar posterior process fractures with open reduction and percutaneous fixation

Abstract: The purpose of this study was to provide an initial assessment of treatment for talar posterior process fractures using open reduction and internal fixation (ORIF) through posteromedial approach and percutaneous screw fixation. From January 2014 to December 2018, 12 cases with displaced fracture of talar posterior process were treated in our department. The clinical and radiological results were assessed after 4 and 12 months of operation with Visual Analog Scale (VAS) pain and American Orthopedic Foot and Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Cedell [4] described the avulsion fracture of the posteromedial tubercule during forced pronation and dorsiflexion of the foot. The rarer mechanism is the direct trauma of the posteromedial facet by the impingement of the sustentaculum during supination and forced dorsiflexion with injuries caused by high intensity forces [5].…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Cedell [4] described the avulsion fracture of the posteromedial tubercule during forced pronation and dorsiflexion of the foot. The rarer mechanism is the direct trauma of the posteromedial facet by the impingement of the sustentaculum during supination and forced dorsiflexion with injuries caused by high intensity forces [5].…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…The talus is a critical link between the leg and the foot, playing an important role in normal ambulation [ 1 ]. The posterior process of the talus (PPOT) is a bony process at the posterior part of the talus body, consisting of the lateral and medial tubercles, which are separated by a groove for the flexor hallucis longus tendon situated in between the two tubercles [ 2 , 3 ]. The lateral tubercle is the larger of the two projects and attached to the posterior talofibular ligament and the posterior talofibular ligament [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight bearing per unit area of talus is very high and it has complex anatomical relation with other structure. So accurate reduction is essential to maintain articular surface integrity [4] . Various literature review revealed that there is variability in the outcome of treatment of talus fracture.…”
Section: Introductionmentioning
confidence: 99%